2019
DOI: 10.4103/1735-5362.263627
|View full text |Cite
|
Sign up to set email alerts
|

Klotho induces insulin resistance possibly through interference with GLUT4 translocation and activation of Akt, GSK3β, and PFKfβ3 in 3T3-L1 adipocyte cells

Abstract: Klotho is considered as an anti-aging factor inducing insulin resistance and involved in type 2 diabetes. However, mechanisms by which klotho induces insulin resistance remain to be understood. Thus, in this study, we aimed to evaluate possible interference points of klotho with insulin signaling pathways in 3T3-L1 adipocyte cells by focusing on phosphorylation levels of Akt, GSK3β, PFK-fβ3, and GLUT4 translocation. Differentiation of 3T3-L1 cells to the adipocyte-like cells were performed using specific diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Still, these results were reversed after klotho overexpression. This was consistent with the fact that klotho could reduce the phosphorylation of Akt to weaken insulin signal transduction [ 22 ]. These results suggested that klotho gene knockdown could activate the IGF-1/PI3K/Akt/mTOR signaling pathway in trophoblast cells.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Still, these results were reversed after klotho overexpression. This was consistent with the fact that klotho could reduce the phosphorylation of Akt to weaken insulin signal transduction [ 22 ]. These results suggested that klotho gene knockdown could activate the IGF-1/PI3K/Akt/mTOR signaling pathway in trophoblast cells.…”
Section: Discussionsupporting
confidence: 86%
“…Still, these results were reversed after klotho overexpression. is was consistent with the fact that klotho could reduce the phosphorylation of Akt to weaken insulin signal transduction [22].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This weakens intracellular signal transduction, prevents the translocation of Glucose Transporter Type 4, and triggers insulin resistance in adipocytes. [25,26] Furthermore, Klotho plays a significant role in the internal regulation of insulin activity as a negative feedback mechanism: insulin promotes the shedding of Klotho, elevating serum Klotho protein levels, thereby hindering peripheral insulin signaling and blocking extended insulin activity. [27] On the other hand, some studies have found that in T2DM mice models, Klotho could improve insulin sensitivity and hepatic glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The Klotho gene is located on Chromosome 13 and has a length of 1012 amino acids (25). The Klotho gene codes for the protein Klotho (KL), which is an anti-aging protein that protects oxidative stress (25), provides insulin resistance (26), and aids calcium homeostasis (27). The KL-VS variant of the Klotho gene plays a role in AD pathology.…”
Section: Klothomentioning
confidence: 99%